Evaluation of outsourcing companies of waste electrical and electronic equipment recycling - Kara, S. S. (CTR ENVIRONMENT & ENERGY RESEARCH & STUDIES, 2011)
An increasing number of companies have focused on reducing the amount of waste properly or gaining value from used products. Facilitating the reverse flow of used products from consumers to manufacturers is a difficult and expensive process depending on the product and transportation type and distance. Another alternative is to outsource these activities. Outsourcing management helps companies for better using of time, energy, labor, technology, capital, resources etc. Moreover, working with wrong partners effects manufacturers' financial and operational situations. In order to get the best services, manufacturers usually invite several outsourcing companies for providing their tenders and then select the best offer. In this stage, using mathematical decision making techniques may help decision makers to get realistic results. In this paper the proposed methodology integrates two multi-criteria decision methods for ranking alternatives. This methodology is applied to a mid-sized firm operating in the field of electrical and electronic equipment. The results indicate that the most important criterion is cost for determining the best alternative. Besides, as it can be seen from the results, the best alternative for the manufacturer is the second alternative. These results propose a guideline for manufacturers for selecting the best alternative. From the results it can easily be seen that this approach shows its potential advantage in selecting suitable alternative due to its sound logic and easily programmable computation procedure.
Keywords: Electronic recycling; Fuzzy analytical hierarchy process; Outsourcing management; MULTICRITERIA DECISION APPROACH; MANAGEMENT; SELECTION; METHODOLOGY; INDUSTRY; SYSTEMS; CYPRUS; Environmental Sciences & Ecology